Implementation of the Infant-Toddler Checklist in Swedish child health services at 18 months: an observational study - Anna Erica Fäldt; Anna Levin; Anton Dahlberg (BMJ Paediatrics Open, 2024)
Background Communication and language disorders are common conditions that emerge early and negatively impact quality of life across the life course. Early identification may be facilitated using a validated screening tool such as the Infant-Toddler Checklist (ITC). We introduced the ITC at the 18-month visit to child health services (CHS) in a Swedish county. Using the RE-AIM implementation framework, this study assessed the implementation of the ITC according to five key dimensions: reach, effectiveness, adoption, implementation and maintenance.Methods This observational study used medical records at CHS as data source. Data were collected from children who visited a child health nurse at 17–22 months. The sample included 2633 children with a mean age of 17.8 months, 1717 in the pre-implementation group and 916 in the post implementation group. We calculated the ITC completion rate (reach) and use at each site (adoption). We compared rates of referral to speech and language therapy (effectiveness) before and after implementation of the ITC using OR and 95% CIs. We described actions to facilitate implementation and maintenance of ITC screening over time.Results The overall screening rate was 93% (reach) which increased from 80% initially to 94% at the end of the 2-year period (maintenance). All centres used the ITC (adoption). The ITC screen positive rate was 14%. Of children who had reached at least 24 months (n=2367), referral rate was 0.4% pre-implementation versus 6.9% post implementation (OR=18.17, 95% CI 8.15, 40.51, p<0.001) (effectiveness). Implementation strategies included training sessions, collaboration, written and automatic procedures and modifications to the medical records system.Conclusion The implementation of the ITC was associated with high reach, higher referral rate, complete adoption, and sustained maintenance over time.